Perbandingan efektivitas kompres hangat dan kompres dingin terhadap penurunan dismenorea pada remaja putri - Oktasari, Gayatri -; -, Misrawati -; Utami, Gamya Tri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this study was to compare the effectiveness of a warm compress and cold compress to decrease dysmenorrhea in adolescent girls. The design of this research was "Quasy experiment" by "pre-test and post-test designs with two comparison treatments". This study was conducted to young girls in Junior High School 21 Pekanbaru. Total sample of 50 people were taken by purposive sampling technique with attention to inclusion criteria. Measuring instruments used a numeric rating scale to measure pain intensity. The analysis of this study used univariate and bivariate using Wilcoxon test and Mann-Whitney test. The results of this research showed that is a difference of mean rank after treatment in the group warm compress and cold compress groups with p-value 0.000 < α (0.05). Comparison of Mean rank obtained between changes in pain intensity on a cold compress larger groups are 34.44 while the warm compress is 16.56. This means that there are significant differences between warm compresses and cold compresses in reducing dysmenorrhoea. Judging from the magnitude of change in pain intensity was concluded that cold compresses more effectively than warm compresses to decrease dysmenorrheal. In conclusion this study can be used as a cold compress one nonpharmacologic alternatives in reducing the pain of dysmenorrhea. Keywords : Dysmenorrhoea, cold compresses, warm compresses